Modeling of Sugarcane Felling Information System Using the Use Case Driven Object Method - Uce Indahyanti; Rizka Hadiwiyanti (JOINCS (Journal of Informatics, Network, and Computer Science), 2020)
Use case driven object is a method for controlling object-oriented modeling based on functions or operations in the system (use case). Sistem Informasi Tebang Angkut Tebu (SITAT) is an operational information system for cutting and transporting sugarcane in a sugar factory. The system was made to improve the method of managing sugarcane plantations, analysis of sugarcane ripening, the process of cutting sugarcane, and the weighing process. Referring to the use case driven object method, this object-based system modeling discussion on SITAT will focus on the stages of designing use case diagrams, use case descriptions, robustness diagrams, and sequence diagrams. The implementation of use case driven method is expected to reduce bad factors, optimize existing resources, improve services to farmers, sugarcane owners or other stakeholders, which will lead to increase efficiency and effectiveness in all processes related to sugarcane transport management.